2016
DOI: 10.1002/jmv.24727
|View full text |Cite
|
Sign up to set email alerts
|

Determination of nasal mucociliary clearance time and nasal symptom in patients with Crimean‐Congo hemorrhagic fever

Abstract: Crimean-Congo hemorrhagic fever (CCHF) is an important health problem in Turkey. Number of studies on symptoms of ear nose throat system and indicating whether or not the organs are affected in patients with CCHF is limited. The aim of the present study was to investigate whether CCHF infections caused any change in nasal physiology in adult patients or not by using saccharin transit time (STT) and nasal symptom scoring. Twenty subjects with laboratory-confirmed diagnosis of CCHF and 28 healthy control subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In 2017, Chinnapaiyan et al [27] reported that HIV infection suppressed tracheobronchial mucociliary clearance and predisposed patients to recurrent lung infections, pneumonia and chronic bronchitis. Similarly, Durmuş et al [28] found that the NMCT was prolonged in adult patients with Crimean-Congo haemorrhagic fever compared with healthy individuals in the control group.…”
Section: Discussionmentioning
confidence: 81%
“…In 2017, Chinnapaiyan et al [27] reported that HIV infection suppressed tracheobronchial mucociliary clearance and predisposed patients to recurrent lung infections, pneumonia and chronic bronchitis. Similarly, Durmuş et al [28] found that the NMCT was prolonged in adult patients with Crimean-Congo haemorrhagic fever compared with healthy individuals in the control group.…”
Section: Discussionmentioning
confidence: 81%
“…Durmus ¸et al 14 found that nasal MCC duration was longer in patients with a diagnosis of laboratory-confirmed CCHF than healthy individuals and that the difference between them was statistically significant. They reported that clinicians should follow CCHF patients more closely for respiratory tract diseases, sinonasal and tympanum infections.…”
Section: Discussionmentioning
confidence: 98%
“…In the literature, studies are showing the change of MCC duration in viral diseases such as Human Immunodeficiency Virus (HIV) and Crimean-congo hemorrhagic fever (CCHF). 14,17 Milgrim et al 17 reported that the duration of nasal MCC in HIV patients was longer than in nonHIV controls, and the difference between them was statistically significant. The authors stated that the prolonged nasal MCC duration correlated with nasal obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting with epistaxis, CCHFV is known to cause various symptoms in terms of Ear Nose Throat (ENT) such as dizziness, hear loss, and nasal congestion. In the literature, we can reach concerning these symptoms; all symptoms except for the dizziness complaint in particular were seen to be evaluated with various previous studies [10][11][12].…”
Section: Introductionmentioning
confidence: 99%